Surgical Esthetic Correction For Gingival Pigmentation - Arinda Rizkya Wakhida; Noer Ulfah (Denta Journal Kedokteran Gigi, 2016)
Background: Aesthetic and health is one aspect that is presently the subject of attention. Abnormalities in symmetrical, gingival color and contour will have the effect of harmonizing the appearance of teeth. Gingival hyperpigmentation occurs due to excessive deposition ofmelanin pigment causing gingival color becomes darker. In general, gingival hyperpigmentation not cause medical problems, but patients often complain about the colorbrown or black gums that are considered disturbing appearance. One of the treatments is esthetic periodontal plastic surgery. Esthetic periodontal plastic surgery is aimed at correcting the gingival hyperpigmentation. Purpose: The purpose of this study is to understand the management of esthetic periodontal plastic surgery for Gingival hyperpigmentation. Case: 21 year old female patient came to clinic with chief complain ofgreyish gingival color and has no confidence of smiling. Case Management: Anterior-maxilla and mandible gingival hyperpigmentation was performed using scalpel #15. Orban knife was used to shape interdental area, followed by saline irrigation. Periodontal pack is placedaround the surgical area. Conclusion: Esthetic periodontal plastic surgery using scalpel is often used to achieve gingival esthetics. Wound healing process is reported fine, as painless and no infection occur.